Analisis Ergonomi Terhadap Desain Mebel Pada Sekolah Anak Usia Dini Dengan Antropometri Anak Usia 2 – 3 Tahun - Novita Siaul; Mariana Wibowo; M. Taufan Rizqy (Intra, 2018)
Early childhood schools have the goal of meeting the needs of children in education both academically, socially and emotionally. This study discusses the ergonomics of furniture design in early childhood education system with anthropometry of early child age 2-3 years. The research method used in this research is quantitative research with survey esplanation format and the result of this research is the calculation of percentile of body dimension of early child in early child school in Surabaya. This research was conducted at 5 international schools and 5 PAUD in Surabaya so that later will create a measure that can be reference of furniture size for early child school in Surabaya.